A cross-sectional study of triallate exposure and neurological health among workers at a pesticide manufacturing and formulating facility. Issue 11 (11th October 2004) - Sathiakumar, N; Delzell, E; MacLennan, P A; Anne, M; Rosenberg, N L; Cheng, H; Myers, S L
Abstract : Aims: To evaluate the relation between an indicator of cumulative exposure to triallate and selected measures of neurological function, including nerve conduction, the prevalence of certain neurological deficits as determined by a medical examination, and vibration perception threshold testing in workers at a pesticide manufacturing plant. Methods: Subjects were 50 workers with high estimated triallate exposure ("high triallate" group) and 50 workers with no or low triallate exposure ("no/low triallate" group). Industrial hygienists used existing work histories and personal knowledge of plant operations to develop a triallate score. In-person interviews elicited information on past medical history and on occupational and non-occupational exposures. A neurologist carried out nerve conduction tests of the sural and the peroneal nerves, a standardised neurological examination, and vibration sensation testing. Results: Differences between the high and the no/low triallate groups were minimal for all but one of the six nerve conduction tests, for the prevalence of neurological abnormalities, and for vibration sensation perception. The high triallate group had lower mean sural nerve peak amplitude than the no/low triallate group (11.7 v 15.2 µV, p = 0.03). This difference was reduced when adjusted for other potential risk factors (12.5 v 14.5 µV, p = 0.25) and was not associated with cumulative triallate score. We also noted several associations between factors other than triallate and nerve conduction measures. Conclusion: The results were consistent with the absence of an association between triallate and measures of neurological function.